Lymphocytic Choriomeningitis Virus (LCMV): Current Status and Future Directions for Clinical and Molecular Diagnostic Techniques - Eslami, Narges; Jahanabadi, Somaye; Ziaei, Elham; Shenagari, Mohammad; Salmanzadeh, Shokrollah; Abbasi, Samaneh; Zandi, Milad (Journal of Liaquat University of Medical & Health Sciences, 2024)
Lymphocytic choriomeningitis virus is an RNA virus that is often overlooked despite the potential to cause severe illness. It is a significant cause of viral meningitis, particularly in specific clinical situations. LCMV is transmitted to humans when they come into contact with the secretions of infected mice, and its strong neurotropism primarily results in neurological symptoms. The most vulnerable populations are fetuses and immunosuppressed individuals. LCMV infection acquired through various means can manifest with a wide range of clinical symptoms, varying from being asymptomatic to severe manifestations. Additionally, in cases where individuals are affected by this viral infection, it can result in fatal central nervous system disorders. Specifically, in pregnant women, intrauterine LCMV infection has been observed to lead to fetal or neonatal mortality. Furthermore, it can cause chorioretinitis and hydrocephalus in infants, which not only causes significant harm but also results in long-term impairments. Timely identification and immediate intervention are crucial in improving the prognosis, especially among high-risk groups and regions where the infection is prevalent. Failure to promptly diagnose the condition can lead to significant mortality rates and leave survivors with long-term neurological complications. Consequently, it is imperative to utilize the most appropriate laboratory diagnostic approach, considering the patient's clinical symptoms, exposure history to the virus, and the prevalence of the pathogen in the area, to facilitate accurate clinical detection. This comprehensive review encompasses various diagnostic methodologies employed in managing LCMV, encompassing clinical manifestations, diagnosis, treatment, and potential complications associated with viral infections affecting the central nervous system.